The Longstaffe Collection 1959-1984 : Selected View. - Farrel-Ward, Lorna (Vancouver : Vancouver Art Gallery, 1985)
Anergna, Anirnik ; Appel, Karel ; Bacon, Francis ; Ballachey, Barbara ; Bates, Maxwell ; Baxter, Iain ; Bergeron, Suzanne ; Besant, Derek ; Bush, Jack ; Calder, Alexander ; Carr, Emily ; Chagall, Marc ; Christo ; Close, Chuck ; Colville, Alex ; Cosgrove, Stanley ; etc.
The Longstaffe Collection 1959-1984 : Selected View, Vancouver Art Gallery, Vancouver, January 12 to February 24, 1985
English
kunstcatalogus